INTERGRATION OF THE MINIMUM AGE LIMIT FOR MARRIAGE IN A CHILD PROTECTION PERSPECTIVE IN INDONESIA - Nasywa Nabilah Nugroho; Ramadhan Syahmedi; Fatimah Fatimah (Journal Analytica Islamica, 2026)
This study examines the regulation of the minimum marriage age in Indonesia from the perspectives of child protection and Islamic law. The issue is grounded in the persistence of child marriage despite the enactment of Law Number 16 of 2019, which equalizes the minimum marriage age for men and women at 19 years as a follow-up to Constitutional Court Decision Number 22/PUU-XV/2017. This research employs a normative juridical method using statutory, conceptual, and Islamic law approaches. The findings show that the minimum marriage age regulation is normatively aligned with the principles of child protection, gender equality, and maqashid sharia, particularly through the concepts of baligh, rusyd, and maslahah. However, its implementation remains ineffective due to the frequent use of marriage dispensation, strong cultural and economic pressures, and low public legal awareness. The novelty of this study lies in its integrative analysis of state law and Islamic legal principles in assessing the effectiveness of minimum marriage age regulation as an instrument for preventing child marriage. This study emphasizes the need for stricter judicial supervision, stronger legal literacy, and community-based prevention strategies to ensure comprehensive child protection.